Bread revolution ebook World-class baking with sprouted and whole grains, heirloom flours, and fresh techniques. - Reinhart, Peter (2014)
Renowned baking instructor, and author of The Bread Baker’s Apprentice, Peter Reinhart explores the cutting-edge developments in bread baking, with fifty recipes and formulas that use sprouted flours, whole and ancient grains, nut and seed flours, alternative flours (such as teff and grape skin), and allergy-friendly and gluten-free approaches. A new generation of bakers and millers are developing innovative flours and baking techniques that are designed to extract the grain’s full flavor potential—what Reinhart calls “the baker’s mission.” In this lushly photographed primer, Reinhart draws inspiration from these groundbreaking methods to create master recipes and formulas any home baker can follow, including Sprouted Sandwich Rye Bread, Gluten-Free Many-Seed Toasting Bread, and Sprouted Wheat Croissants. In many instances, such as with sprouted flours, preferments aren’t necessary because so much of the flavor development occurs during the sprouting phase. For grains that benefit from soakers, bigas, and sourdough starters, Reinhart provides the precise guidance that has made him such a trusted expert in the field.   Advanced bakers will relish Reinhart’s inventive techniques and exacting scientific explanations, while beginning bakers will rejoice in his demystification of ingredients and methods—and all will come away thrilled by bread’s new frontier. *Correction to the Sprouted Whole Wheat Bread recipe on page 63: The volume measure of water should be 1 ¾ cups plus 1 tablespoon, not 3 ¼ cups.